2003
DOI: 10.1088/0305-4470/36/45/010
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement for a two-parameter class of states in 2  nquantum system

Abstract: Abstract. We exhibit a two-parameter class of states ρ (α,γ) , in 2 ⊗ n quantum system for n ≥ 3, which can be obtained from an arbitrary state by means of local quantum operations and classical communication, and which are invariant under all bilateral operations on 2 ⊗ n quantum system. We calculate the negativity of ρ (α,γ) , and a lower bound and a tight upper bound on its entanglement of formation. It follows from this calculation that the entanglement of formation of ρ (α,γ) cannot exceed its negativity. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…This recovers previous results obtained by the authors in [19], where Λ = max[ ρ TA , R(ρ) ], and others in [29], where Λ = ρ TA . In addition Eq.…”
supporting
confidence: 91%
“…This recovers previous results obtained by the authors in [19], where Λ = max[ ρ TA , R(ρ) ], and others in [29], where Λ = ρ TA . In addition Eq.…”
supporting
confidence: 91%
“…We outline here the main arguement from Ref. [33]. It was shown that there exist unitary operators U k and probabilities p k such that…”
mentioning
confidence: 94%
“…The class of quantum states with two real parameters α and γ in a 2 ⊗ d quantum system [50] is given as…”
Section: Two Parameter Class Of Statesmentioning
confidence: 99%